A gel polymer electrolyte based on composite of nonwoven fabric and methyl cellulose with good performance for lithium ion batteries. Issue 65 (16th July 2015) - Li, Minxia; Wang, Xiaowei; Wang, Yanfang; Chen, Bingwei; Wu, Yuping; Holze, Rudolf
<x xml:space="preserve">Abstract</x> A new composite gel polymer membrane of nonwoven fabric (NWF) and methyl cellulose (MC) exhibiting good mechanical property and outstanding thermal and electrochemical stability is prepared by simple casting green process.